Enhancing Productivity and Retention in Indonesia’s Gig Economy: The Role of Work-Life Balance, Job Satisfaction, Work Engagement, and Technological Support - Nurnaningsih; Safrida; Isiswanty; Rohman, Azura Zeyna (Universitas Brawijaya, Indonesia, 2025)
The growth of Indonesia’s gig economy has reshaped labor structures, raising urgent questions about how to sustain gig workers’ well-being and productivity. This study examines the impact of trust in the platform, platform fairness, and social support on work-life balance and how work-life balance in turn influences job satisfaction, work engagement, productivity, and employee retention. It also examines the mediating roles of satisfaction and engagement, as well as the moderating effects of technological support and gig work characteristics. Using a quantitative approach, data were collected from 400 gig workers across various platforms, including Gojek, Grab, Shopee, and Freelancer.com, via stratified sampling. A pilot study with 50 workers refined the instrument. Structural equation modeling with SmartPLS 4.0 was employed for analysis, which included confirmatory factor analysis and assessments of reliability, validity, and common method bias. The results show that all three antecedents have a significant impact on work-life balance, which, in turn, improves job satisfaction, engagement, productivity, and retention. Mediators and moderators strengthen these relationships. This study extends the Job Demands-Resources model into the gig economy and offers practical guidance for platform companies to design more supportive and sustainable work environments.